Personaliti dan tahap kepuasan kerja juruteknik di Syarikat Matsushita Air-Conditioning Group of Companies (MACG), Petaling Jaya, Selangor - Lau, Siew Lee (Universiti Malaysia Sarawak, (UNIMAS), 1997)
The purpose of the study is to obtain information on job satisfaction and personality dimensions among technicians in Matsushita Air-Conditioning Group of Companies (MACG), a Japanese international organization located in Malaysia. The study draws on Hofstede 's concept and classification of national culture to predict that job satisfaction will be higher for technicians in certain cultures of nations. A set of questionnaire was distributed to 100 technicians to get the needed information. Job satisfaction in this study consists of four main factors, which are the work itself, promotion, supervisor and co-workers. Mean while, the personality dimension consists of uncertainty avoidance, masculinity femininity, individualism collectivism and power distance. The result shows that technicians possessed positive satisfaction towards the works itself (mean =3.28), followed by promotion (mean = 3.17), and neutral towards co-workers and supervisor (mean = 3.0). Although they show positive satisfaction, however the level is still considered low. Besides that, the result shows that those MACG technicians are characterized by strong femininity, followed by collectivism, uncertainty avoidance and power distance. It is found that the correlation between personality dimensions and job satisfaction is positive and significant. Furthermore, some personality dimensions are significantly correlated to some factors of job satisfaction (r = .305, p <.01), Finally, it is also found uncertainty avoidance was the most important personality dimension that influences the level of job satisfaction among technicians in MACG. The findings from this study may give a wide implication to the management team, especially Human Resource practitioners. It can be used as a base to arrange and organize job as well as to emphasize on the self development or training program. An organization should modify their management practices to suit its goal without neglecting the personality dimensions of employees which may affect their attitudes.